Effects of educational intervention on women’s knowledge and uptake of cervical cancer screening in selected hospitals in Ibadan, Nigeria (2017)
This study evaluated the effects of an educational intervention (El) on women's knowledge and uptake of cervical cancer screening (CCS) services. A quasi-experimental study, conducted in the antenatal clinics of eight hospitals in Ibadan, Nigeria. The hospitals were randomly clustered into four in intervention group (IG) and four in control group (CG), and 846 women were selected in the two groups using Systematic random sampling at baseline and post-intervention (PI). Data were collected using a structured questionnaire. The women in the IG received educational intervention provided by hospital nurses who were exposed to an educational programme previously. Data were analysed using descriptive statistics and x2 at p <0.05. The mean age for women was 28 years ±5.8. The respondents' awareness of CC at baseline was IG: 12.9% and CG: 18.2% but this increased to 71.5% in IG and 22.1% in CG with net intervention effect (NIE) of 54.7% (p <0.0001), knowledge of the causative organism (NIE <37%, p < 0.0001), sexual intercourse as mode of transmission (NIE 53.7%, p<0.001). Screening for early detection of cervical cancer (NIE 75.6%, p < 0.001), awareness of where to receive screening (NIE 64.1%, p < 0.001). There was only a very slight increase in uptake of CCS from 1.4% at baseline to 3.6% in the IG and 2.1 to 2.3% in the CG. Over, 53.5% said unavailability of services was a major hindrance to their screening uptake. Cervical cancer screening knowledge improved in the intervention group but uptake only improved slightly with the intervention. Educational intervention is a useful tool for improving knowledge of Cervical Cancer Screening.